Identifying hearing care access barriers among older Pacific Island people in New Zealand: a qualitative study. Issue 8 (5th August 2019) - Reddy, Ravi; Welch, David; Lima, Ieti; Thorne, Peter; Nosa, Vili
Abstract : Objectives: Hearing loss is one of the most prevalent conditions affecting older people. In addition, there is little known about the factors influencing the uptake of hearing services among underserved communities. Our objective was to identify the barriers to accessing hearing care services among older Pacific Island people in New Zealand. Settings: Eligible participants from Auckland City, New Zealand. Participants: Individual face-to-face in-depth interviews were conducted with 36 older Pacific Island people who were experienced hearing difficulties. Methods: A Pacific Island research methodology ( Talanoa ) and the 'Health Care Access Barriers' (HCAB) model, which identifies modifiable barriers to healthcare, was used as a theoretical framework for this research. The interviews were transcribed and analysed using a deductive approach to identify HCAB themes and subthemes experienced by older Pacific Island people. Results: Identified themes aligned with HCAB's themes of financial, structural and cognitive barriers and subthemes described Pacific Island perspectives related to hearing care access in New Zealand. The financial barriers related to the high cost of hearing care and the structural barriers included transportation difficulties, limited family support, preference for community-based services and the absence of hearing care delivered by family doctors. Community norms and attitudes, communication limitations and limited awareness of hearing care services formed cognitive barriers among older Pasifika people in this study. Conclusion: We identified financial, structural and cognitive barriers that dissuaded older Pasifika people from accessing hearing care services. These modifiable barriers need to be eliminated or minimised to enable people to readily receive the hearing care assistance they need. It is essential to improve and develop culturally responsive models of hearing service delivery to ensure equitable access to hearing care, especially for underserved groups such as Pacific Island communities.